The 'genetic zipper' method offers a cost-effective solution for aphid control - Oberemok, Vol V.; Puzanova, Yelizaveta V.; Gal’chinsky, Nikita V. (Frontiers in Insect Science, 2024)
Twenty years ago, it was difficult to imagine the use of nucleic acids in plant protection as insecticides, but today it is a reality. New technologies often work inefficiently and are very expensive; however, qualitative changes occur during their development, making them more accessible and work effectively. Invented in 2008, contact oligonucleotide insecticides (olinscides, or DNA insecticides) based on the CUAD (contact unmodified antisense DNA) platform have been substantially improved and rethought. The main paradigm shift was demonstrating that unmodified antisense DNA can act as a contact insecticide. Key breakthroughs included identifying convenient target genes (rRNA genes), mechanism of action (DNA containment), and discovering insect pests (sternorrhynchans) with high susceptibility to olinscides. Today, the CUAD platform possesses impressive characteristics: low carbon footprint, high safety for non-target organisms, rapid biodegradability, and avoidance of target-site resistance. This next-generation class of insecticides creates opportunities for developing products tailored for specific insect pest populations. The ‘genetic zipper’ method, based on CUAD biotechnology, integrates molecular genetics, bioinformatics, and in vitro nucleic acid synthesis. It serves as a simple and flexible tool for DNA-programmable plant protection using unmodified antisense oligonucleotides targeting pest rRNAs. Aphids, key pests of important agricultural crops, can be effectively controlled by oligonucleotide insecticides at an affordable price, ensuring efficient control with minimal environmental risks. In this article, a low-dose concentration (0.1 ng/µL; 20 mg per hectare in 200 L of water) of the 11 nt long oligonucleotide insecticide Schip-11 shows effectiveness against the aphid Schizolachnus pineti, causing mortality rate of 76.06 ± 7.68 on the 12th day (p<0.05). At a consumption rate of 200 L per hectare, the cost of the required oligonucleotide insecticide is about 0.5 USD/ha using liquid-phase DNA synthesis making them competitive in the market and very affordable for lab investigations. We also show that non-canonical base pairing Golinscide: UrRNA is well tolerated in aphids. Thus, non-canonical base-pairing should be considered not to harm non-target organisms and can be easily solved during the design of oligonucleotide insecticides. The ‘genetic zipper’ method, based on CUAD biotechnology, helps quickly create a plethora of efficient oligonucleotide pesticides against aphids and other pests. Already today, according to our estimations, the ‘genetic zipper’ is potentially capable of effectively controlling 10-15% of all insect pests using a simple and flexible algorithm.